Alterations in Haematological and Clotting Profile of Post-Menopausal Women in Benin City, Nigeria - Ebengho MI; Obazelu PA; Emokpae MA (Annals of Health Research, 2022)
Background: The cessation of ovarian functions at menopause and the accompanying decline in the production of ovarian steroid hormones creates a unique set of health concerns for women. Reductions in sex steroid levels, particularly oestrogen, have been associated with various diseases and conditions, including bleeding disorders, coronary heart disease (CHD), osteoporosis, cognitive dysfunction, urinary incontinence, hot flushes, and mood changes, among others.